PENGEMBANGAN BUKU TEKS PERADABAN TRANSPORTASI LAUT BERBASIS PROJECT BASED LERANING SEBAGAI STRATEGI PENDIDIKAN KARAKTER RASA INGIN TAHU ANAK - Safitri, Destri; Ari Nugrahanta, Gregorius (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The low level of active engagement and exploratory capacity among elementary school students in conventional, teacher-centered learning environments poses a significant obstacle to early childhood character building. This research focuses on developing a maritime transportation civilization textbook integrated with Project-Based Learning (PjBL) via a genetic approach, employing the ADDIE (Analyze, Design, Develop, Implement, Evaluate) development model to foster children's curiosity character. The research subjects involved 55 fourth-grade students at a public elementary school in Sleman Regency, Yogyakarta, divided into an experimental group (class IV A) and a control group (class IV B). The developed product was implemented through five maritime-themed project activities: constructing miniature ships using recycled cans, ice cream sticks, straws, used bottles, and cardboard. Based on the findings, the developed textbook achieved an average expert validation score of 3.78, categorized as